THE ROLE OF EMOTIONAL INTELLIGENCE IN EDUCATIONAL COMMUNICATION WITHIN THE LEARNING PROCESS OF ISLAMIC RELIGIOUS EDUCATION - St. Wardah Hanafie Das; M. Muharrir Na'iem; Nurhidaya Da’te (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
Emotional intelligence has increasingly gained attention as a crucial psychological competence in educational studies, particularly in relation to the effectiveness of communication between educators and learners. This article aims to provide an in-depth analysis of the role of emotional intelligence in educational communication within the learning process of Islamic Religious Education (IRE), emphasizing the integration of educational psychology, pedagogical perspectives, and Islamic values. This study employs a qualitative method with a library research approach by critically reviewing relevant academic literature, educational journals, and Islamic sources, including the Qur’an, Prophetic traditions, and classical Islamic scholars’ works. The findings reveal that emotional intelligence plays a strategic role in shaping effective, humane, and character-oriented educational communication. Educators with high emotional intelligence are better able to regulate emotions, develop empathy, and create a psychologically safe learning environment, thereby preventing verbal and non-verbal violence in educational settings. Furthermore, the integration of emotional intelligence into IRE learning communication significantly contributes to strengthening moral internalization, role modeling, and positive discipline among students. The novelty of this article lies in its comprehensive conceptual framework that integrates emotional intelligence theory with Islamic educational values and classical scholarly perspectives, an area that has received limited scholarly attention. This article is expected to serve as both a theoretical reference and a practical guideline for Islamic education educators in developing emotionally intelligent and character-based educational communication practices.